Multi-element filler modified polyurethane hydrogen-resistant coating and preparation process thereof

Through the dense structure and efficient preparation process of multi-filler modified polyurethane hydrogen-resistance coating, the problem of low hydrogen embrittlement and coating bonding in the prior art is solved, and efficient hydrogen shielding effect and long-life coating application are achieved.

CN119192979AActive Publication Date: 2024-12-27河南省锅炉压力容器检验技术科学研究院

Patent Information

Application Number
CN202411600914.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing hydrogen-resistance coating is prone to hydrogen embrittlement and hydrogen damage in high-pressure hydrogen-rich environments, and the preparation process is complex, making it difficult to apply on large-scale pipes and special-shaped parts. It has low bonding, poor thermal shock resistance, and is prone to cracking. Peel off.

Method used

Using a multivariate filler modified polyurethane hydrogen-resistance coating, the chemical components include polyurethane prepolymer, dispersant, NbSe2, silane modified graphene and Ti2SnC, and are prepared by sandblasting treatment, heating, magnetic stirring and ultrasonic defoaming. Dense coating structure improves hydrogen resistance and bonding.

Benefits of technology

It significantly improves the penetration shielding effect of hydrogen and its isotopes, extends the service life of 316L stainless steel material, has a dense coating structure and a firm bonding, excellent hydrogen resistance effect, simple preparation process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192979A_ABST
    Figure CN119192979A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of organic coatings, and particularly relates to a multi-filler modified polyurethane hydrogen-resistant coating and a preparation process thereof.The polyurethane hydrogen-resistant coating is prepared from, by mass, 59.5%-61.3% of a polyurethane prepolymer, 20.3%-23.1% of a dispersing agent, 2.17%-2.84% of NbSe2, 10.9%-12.2% of a curing agent, 1.62%-2.26% of silane modified graphene and 1.08%-1.52% of Ti2SnC. The polyurethane hydrogen-resistant coating is simple in preparation process, low in cost and suitable for industrial production. The structure is compact and the hydrogen-resistant effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic coatings, and in particular to a multi-filler modified polyurethane hydrogen barrier coating and a preparation process thereof. Background Art

[0002] As a clean green energy, hydrogen energy has the advantages of being pollution-free, high in calorific value, and renewable and cyclical. It is hailed as the most promising secondary energy source in the future. However, the problem of hydrogen damage to hydrogen energy storage and transportation materials is one of the key problems currently restricting the industrialization of hydrogen energy. This is because metal materials have been in service for a long time in a high-pressure hydrogen-rich environment, and hydrogen inevitably enters the interior of the material through penetration and diffusion, making the material prone to problems such as hydrogen embrittlement and hydrogen damage, which seriously affects the stable operation of the hydrogen storage and transportation system, and even causes serious safety accidents, causing irreparable losses to people's lives and property.

[0003] Due to its excellent corrosion resistance and mechanical properties, 316L stainless steel is widely used in hydrogen storage equipment, reactor blanket structure and other fields. In order to reduce the corrosion and damage of hydrogen and its isotopes to austenitic stainless steel materials, a hydrogen barrier coating is generally prepared on the surface of the material to set a hydrogen permeation barrier, which plays a role in slowing down or preventing hydrogen and its isotopes from entering the substrate, thereby preventing the occurrence of hydrogen embrittlement and other phenomena. This is currently a relatively economical and effective means.

[0004] At present, the hydrogen barrier coatings used on a large scale are mainly ceramic coatings, including oxide coatings (Er2O3, Al2O3, ZrO2, SiO2, TiO2, Cr2O3, etc.) and non-oxidation coatings (TiN, Fe2N, AlN, TiC, SiC, etc.). They have good hydrogen barrier properties, and the preparation methods are mainly magnetron sputtering, chemical vapor deposition, micro-arc oxidation, plasma spraying, sol-gel method, etc. However, their preparation processes are often more complicated and demanding, and are not easy to be used on a large scale on pipelines and special-shaped parts. In addition, this type of hydrogen barrier coating and the substrate material also have problems such as low bonding, poor thermal shock resistance, and easy cracking and peeling.

[0005] Polyurethane coatings are widely used in the field of material surface protection due to their good flexibility, wear resistance, weather resistance and other characteristics. However, there are relatively few research and applications on polyurethane hydrogen barrier coatings in China. The development and design of new polyurethane hydrogen barrier coatings and their preparation processes have important scientific significance and economic value. Summary of the invention

[0006] In view of the above-mentioned defects and problems, the present invention provides a multi-filler modified polyurethane hydrogen barrier coating and a preparation process thereof, which has a simple preparation process, a dense structure, and a good hydrogen barrier effect. It can be applied to the polyurethane hydrogen barrier coating on the surface of 316L stainless steel material to meet the requirements of practical engineering applications.

[0007] The solution adopted by the present invention to solve its technical problem is: a multi-filler modified polyurethane hydrogen barrier coating, the mass percentage of the chemical components of the polyurethane hydrogen barrier coating is: polyurethane prepolymer: 59.5-61.3%, dispersant: 20.3-23.1%, NbSe2: 2.17-2.84%, curing agent: 10.9-12.2%, silane-modified graphene: 1.62-2.26%, Ti2SnC: 1.08-1.52%, and the sum of the mass percentages of each chemical component is 100%.

[0008] Furthermore, the curing agent is 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), and the dispersant is ethyl acetate.

[0009] Furthermore, the polyurethane prepolymer is a polyether polyurethane prepolymer; NbSe2 is nano NbSe2; and Ti2SnC is nano Ti2SnC.

[0010] Furthermore, the mass percentages of the chemical components of the multi-filler modified polyurethane hydrogen barrier coating are: polyurethane prepolymer: 60.5%, curing agent: 11.5%, dispersant: 22.3%, NbSe2: 2.5%, silane-modified graphene: 1.9%, Ti2SnC: 1.3%, and the sum of the mass percentages of each chemical component is 100%.

[0011] Furthermore, a preparation process of a multi-filler modified polyurethane hydrogen barrier coating comprises the following steps: (1) Pretreatment of 316L stainless steel: Use a sandblasting machine to sandblast the 316L stainless steel material to remove oxide scale, grease, etc. until the metallic luster is exposed, forming a rough surface with a frosted texture. Then wipe it clean with anhydrous ethanol or acetone, dry it naturally, and put it in a sealed bag for later use; (2) Weighing a polyurethane prepolymer, heating it to 75-85° C., and setting it aside; weighing a curing agent, heating it at 125-135° C. until it melts, and setting it aside; (3) weighing a dispersant, then adding silane-modified graphene, NbSe2 and Ti2SnC to the dispersant, and stirring with a magnetic stirrer at a speed of 600-1000 rpm for 20-60 min to fully disperse the silane-modified graphene, NbSe2 and Ti2SnC in the dispersant to obtain a solution A; (4) adding the heated polyurethane prepolymer to solution A, stirring at 800-1200 rpm for 40-90 min using a magnetic stirrer, and then removing internal bubbles using ultrasound to obtain solution B; (5) adding the melted curing agent to solution B, stirring the mixture at 450-750 rpm for 1.5-2.5 h using a magnetic stirrer, and then removing bubbles using ultrasound to obtain a mixed solution C; (6) Using a spin coater, solution C is spin-coated onto the surface of the 316L stainless steel material, and then placed in the air to dry naturally for more than 72 hours and naturally solidify to obtain a polyurethane hydrogen barrier coating.

[0012] Furthermore, the thickness of the prepared polyurethane hydrogen barrier coating is 0.25 to 0.55 mm.

[0013] Furthermore, the polyurethane hydrogen barrier coating is applied to 316L stainless steel material.

[0014] Beneficial effects of the present invention: The hydrogen barrier performance of the polyurethane hydrogen barrier coating not only depends on the composition of the hydrogen barrier material, but is also closely related to the organizational structure, defects, stability, etc. of the hydrogen barrier coating. The multi-filler modified polyurethane hydrogen barrier coating of the present invention has a dense coating structure and no defects. It is firmly combined with the surface of the 316L stainless steel material and has obvious blocking and shielding effects on the penetration of hydrogen and its isotopes. The multi-filler silane-modified graphene, NbSe2 and Ti2SnC introduced into the polyurethane coating can effectively improve the hydrogen barrier effect of the polyurethane coating by combining the three: first, the nano-scale flakes of the silane-modified graphene can directly block the penetration of hydrogen and its isotopes, and graphene is also a good hydrogen trap, thereby blocking the penetration of hydrogen and its isotopes; secondly, NbSe2 and Ti2SnC are both layered structure materials, which can hinder the penetration of hydrogen and Its isotopes penetrate and diffuse in the polyurethane coating, improving the hydrogen barrier properties of the coating. In addition, nano-Ti2SnC has both the ceramic characteristics of high temperature resistance, high strength, and oxidation resistance and the metal characteristics of high thermal conductivity and impact resistance, and has good thermal shock resistance and high temperature stability, giving the polyurethane hydrogen barrier coating good comprehensive performance; thirdly, the multi-element filler can increase the density of the polyurethane coating, which is beneficial to improve the bonding degree between the polyurethane hydrogen barrier coating and the 316L stainless steel material and the hydrogen barrier effect of the coating; the polyurethane hydrogen barrier coating modified by the multi-element filler is firmly bonded to the 316L stainless steel material, the coating structure is dense, and the hydrogen barrier effect is excellent, which can effectively reduce or even prevent the hydrogen damage problem of the 316L stainless steel material and extend its service life; at the same time, the chemical composition of the polyurethane hydrogen barrier coating is scientific, the preparation process is simple, the cost is low, and it is easy to implement, with significant production advantages and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a morphology diagram of the unmodified graphene used in the present invention.

[0016] Figure 2 This is a morphology image of the silane-modified graphene prepared in the present invention. DETAILED DESCRIPTION

[0017] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0018] Example 1. In a specific embodiment of the present invention, the mass percentages of the chemical components of the multi-filler modified polyurethane hydrogen barrier coating are: polyether polyurethane prepolymer: 60.8%, dispersant (ethyl acetate): 22.7%, NbSe2: 2.35%, curing agent (MOCA): 11.24%, silane-modified graphene: 1.68%, Ti2SnC: 1.23%, and the sum of the mass percentages of each chemical component is 100%.

[0019] The preparation process comprises the following steps: (1) Pretreatment of 316L stainless steel: Use a sandblasting machine to sandblast the 316L stainless steel material to remove oxide scale, grease, etc. until the metallic luster is exposed, forming a rough surface with a frosted texture, then wipe it clean with anhydrous ethanol, dry it naturally, and put it in a sealed bag for later use; (2) Weigh the polyether polyurethane prepolymer and heat it to 82°C for later use; weigh the curing agent (MOCA), heat it at 128°C until it melts and set aside; (3) weighing a dispersant, then adding silane-modified graphene, NbSe2 and Ti2SnC to the dispersant, and stirring at 800 rpm for 30 min using a magnetic stirrer to fully disperse the silane-modified graphene, NbSe2 and Ti2SnC in the dispersant to obtain a solution A; (4) adding the heated polyether polyurethane prepolymer to solution A, stirring at 900 rpm for 50 min using a magnetic stirrer, and then removing internal bubbles using ultrasound to obtain solution B; (5) adding the melted curing agent (MOCA) to solution B, stirring at 500 rpm for 2.5 h using a magnetic stirrer, and then removing bubbles using ultrasound to obtain a mixed solution C; (6) Using a spin coater, the mixed solution C was spin-coated onto the surface of 316L stainless steel material with a coating thickness of 0.45 mm. The mixture was then placed in air to dry naturally for 96 hours and cured naturally to obtain a polyurethane hydrogen barrier coating.

[0020] Example 2: A multi-filler modified polyurethane hydrogen barrier coating and its preparation process in this embodiment are described with the differences from Example 1 as the center.

[0021] In this embodiment, the mass percentages of the chemical components of the multi-filler modified polyurethane hydrogen barrier coating are: polyether polyurethane prepolymer: 61.3%, dispersant (ethyl acetate): 21.5%, NbSe2: 2.75%, curing agent (MOCA): 11.0%, silane-modified graphene: 1.93%, Ti2SnC: 1.52%, and the sum of the mass percentages of each chemical component is 100%.

[0022] The preparation process comprises the following steps: (1) Pretreatment of 316L stainless steel: Use a sandblasting machine to sandblast the 316L stainless steel material to remove oxide scale, grease, etc. until the metallic luster is exposed, forming a rough surface with a frosted texture, then wipe it clean with anhydrous ethanol, dry it naturally, and put it in a sealed bag for later use; (2) Weigh the polyether polyurethane prepolymer, heat it to 80°C, and set it aside; weigh the curing agent (MOCA), heat it at 130°C until it melts, and set it aside; (3) Weighing a dispersant (ethyl acetate), then adding silane-modified graphene, NbSe2 and Ti2SnC into the dispersant, stirring at 900 rpm for 25 min using a magnetic stirrer to fully disperse the silane-modified graphene, NbSe2 and Ti2SnC in the dispersant, to obtain a solution A; (4) adding the heated polyether polyurethane prepolymer to solution A, stirring at 800 rpm for 70 min using a magnetic stirrer, and then removing internal bubbles using ultrasound to obtain solution B; (5) adding the melted curing agent (MOCA) to solution B, stirring the mixture at 750 rpm for 1.5 h using a magnetic stirrer, and then removing bubbles using ultrasound to obtain a mixed solution C; (6) Using a spin coater, the mixed solution C was spin-coated onto the surface of 316L stainless steel material with a coating thickness of 0.30 mm, and then placed in the air to dry naturally for 72 hours and naturally solidify to obtain a polyurethane hydrogen barrier coating.

[0023] Example 3: A multi-filler modified polyurethane hydrogen barrier coating and its preparation process in this embodiment are described with the differences from Example 1 as the center.

[0024] In this embodiment, the mass percentages of the chemical components of the multi-filler modified polyurethane hydrogen barrier coating are: polyether polyurethane prepolymer: 59.5%, dispersant (ethyl acetate): 22.48%, NbSe2: 2.84%, curing agent (MOCA): 12.0%, silane-modified graphene: 2.06%, Ti2SnC: 1.12%, and the sum of the mass percentages of each chemical component is 100%.

[0025] The preparation method comprises the following steps: (1) Pretreatment of 316L stainless steel: Use a sandblasting machine to sandblast the 316L stainless steel material to remove oxide scale, grease, etc. until the metallic luster is exposed, forming a rough surface with a frosted texture, then wipe it clean with anhydrous ethanol, dry it naturally, and put it in a sealed bag for later use; (2) Weigh the polyether polyurethane prepolymer, heat it to 85°C, and set it aside; weigh the curing agent (MOCA), heat it at 132°C until it melts, and set it aside; (3) weighing a dispersant (ethyl acetate), then adding silane-modified graphene, NbSe2 and Ti2SnC to the dispersant, and stirring at 750 rpm for 40 min using a magnetic stirrer to fully disperse the silane-modified graphene, NbSe2 and Ti2SnC in the dispersant to obtain a solution A; (4) adding the heated polyether polyurethane prepolymer to solution A, stirring at 1000 rpm for 45 min using a magnetic stirrer, and then removing internal bubbles using ultrasound to obtain solution B; (5) adding the melted curing agent (MOCA) to solution B, stirring the mixture at 700 rpm for 2 h using a magnetic stirrer, and then removing bubbles using ultrasound to obtain a mixed solution C; (6) Using a spin coater, the mixed solution C was spin-coated onto the surface of the 316L stainless steel material with a coating thickness of 0.50 mm, and then placed in the air to dry naturally for 120 hours and naturally cure to obtain a polyurethane hydrogen barrier coating.

[0026] Performance Test: Under room temperature conditions, an electrochemical hydrogen permeation experiment was conducted on the multi-filler modified polyurethane hydrogen barrier coating prepared in the above embodiment. The test results are as follows: 1. The multi-filler modified polyurethane hydrogen barrier coating prepared according to the ratio and process described in Example 1 has a hydrogen permeation resistance that is 74 times that of 316L stainless steel material, and the coating has excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface state of the polyurethane hydrogen barrier coating is good. In addition, the adhesion strength of the polyurethane hydrogen barrier coating was tested, and the result was 3.47MPa, which also proves that the coating is firmly bonded to the 316L stainless steel material.

[0027] 2. The multi-filler modified polyurethane hydrogen barrier coating prepared according to the ratio and process described in Example 2 has a hydrogen permeation resistance that is 80 times that of 316L stainless steel material, and the coating has excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface state of the polyurethane hydrogen barrier coating is good. In addition, the adhesion strength of the polyurethane hydrogen barrier coating was tested, and the result was 3.50MPa, which also proves that the coating is firmly bonded to the 316L stainless steel material.

[0028] 3. The multi-filler modified polyurethane hydrogen barrier coating prepared according to the ratio and process described in Example 3 has a hydrogen permeation resistance that is 70 times that of 316L stainless steel material, and the coating has excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface state of the polyurethane hydrogen barrier coating is good. In addition, the adhesion strength of the polyurethane hydrogen barrier coating was tested, and the result was 3.62MPa, which also proves that the coating is firmly bonded to the 316L stainless steel material.

[0029] In summary, the multi-filler modified polyurethane hydrogen barrier coating provided by the present invention has a dense structure, good hydrogen barrier effect, and a simple preparation process. It can be applied to the polyurethane hydrogen barrier coating on the surface of 316L stainless steel material to meet the requirements of practical engineering applications.

[0030] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-filler modified polyurethane hydrogen barrier coating, characterized in that: The chemical components of the polyurethane hydrogen barrier coating are as follows: polyurethane prepolymer: 59.5-61.3%, dispersant: 20.3-23.1%, NbSe2: 2.17-2.84%, curing agent: 10.9-12.2%, silane-modified graphene: 1.62-2.26%, Ti2SnC: 1.08-1.52%, and the sum of the chemical components' mass percentages is 100%.

2. The multi-filler modified polyurethane hydrogen barrier coating according to claim 1, characterized in that: The curing agent is 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), and the dispersant is ethyl acetate.

3. The multi-filler modified polyurethane hydrogen barrier coating according to claim 1, characterized in that: The polyurethane prepolymer is a polyether polyurethane prepolymer; NbSe2 is nano NbSe2; and Ti2SnC is nano Ti2SnC.

4. The multi-filler modified polyurethane hydrogen barrier coating according to claim 1, characterized in that: The chemical components of the multi-filler modified polyurethane hydrogen barrier coating are as follows: polyurethane prepolymer: 60.5%, curing agent: 11.5%, dispersant: 22.3%, NbSe2: 2.5%, silane-modified graphene: 1.9%, Ti2SnC: 1.3%, and the sum of the chemical components' mass percentages is 100%.

5. A preparation process of a multi-filler modified polyurethane hydrogen barrier coating, applied to the multi-filler modified polyurethane hydrogen barrier coating according to claims 1-4, characterized in that: The following steps are included: (1) Pretreatment of 316L stainless steel: Use a sandblasting machine to sandblast the 316L stainless steel material to remove oxide scale, grease, etc. until the metallic luster is exposed, forming a rough surface with a frosted texture. Then wipe it clean with anhydrous ethanol or acetone, dry it naturally, and put it in a sealed bag for later use; (2) Weighing a polyurethane prepolymer, heating it to 75-85° C., and setting it aside; weighing a curing agent, heating it at 125-135° C. until it melts, and setting it aside; (3) weighing a dispersant, then adding silane-modified graphene, NbSe2 and Ti2SnC to the dispersant, and stirring with a magnetic stirrer at a speed of 600-1000 rpm for 20-60 min to fully disperse the silane-modified graphene, NbSe2 and Ti2SnC in the dispersant to obtain a solution A; (4) adding the heated polyurethane prepolymer to solution A, stirring at 800-1200 rpm for 40-90 min using a magnetic stirrer, and then removing internal bubbles using ultrasound to obtain solution B; (5) adding the melted curing agent to solution B, stirring the mixture at 450-750 rpm for 1.5-2.5 h using a magnetic stirrer, and then removing bubbles using ultrasound to obtain a mixed solution C; (6) Using a spin coater, solution C is spin-coated onto the surface of the 316L stainless steel material, and then placed in the air to dry naturally for more than 72 hours and naturally solidify to obtain a polyurethane hydrogen barrier coating.

6. The process for preparing a multi-filler modified polyurethane hydrogen barrier coating according to claim 5, characterized in that: The thickness of the prepared polyurethane hydrogen barrier coating is 0.25-0.55 mm.

7. The multi-filler modified polyurethane hydrogen barrier coating according to claim 1, characterized in that: The polyurethane hydrogen barrier coating is applied to 316L stainless steel material.

Citation Information

Patent Citations

  • Organic hydrogen permeation-resistant coating as well as preparation method and application thereof

    CN115093769A

  • Composite hydrogen-permeation-resistant coating for hydrogen conveying pipeline and preparation method of composite hydrogen-permeation-resistant coating

    CN115651519A

  • APTES-GO modified PVDF organic hydrogen-resistant coating, coating, preparation method and hydrogen delivery pipeline

    CN116790163A

  • Composite coating for hydrogen pipeline and preparation method of composite coating

    CN117965074A

  • Preparation and application of graphene oxide-polyvinyl alcohol / polyurethane layer-by-layer assembled hydrogen-resistant coating capable of being applied to metal substrate

    CN118290995A

Cited By

  • A hydrogen barrier anticorrosive coating material, a preparation method and application thereof

    CN122686215A